PEMBERDAYAAN PKK BANJAR TOHPATI DESA KESIMAN KERTALANGU SEBAGAI KADER DALAM MENDUKUNG GERAKAN MASYARAKAT CERDAS MENGGUNAKAN OBAT - Wijaya, Made Dharmesti (Buletin Udayana Mengabdi; Vol 19 No 3 (2020): Buletin Udayana Mengabdi, 2020)
Self-medication has been widely carried out by the community to treat various ailments such as headaches, fevers, colds, and others. However, in practice, medication errors often occur due to improper self-diagnosis, dosage errors, drug misuse, or biased information from drug advertisements. Irrational self-medication management may lead to negative effects such as undesirable therapeutic effects or adverse drug reactions. Therefore, we carried out a community empowerment program to our partner, PKK Banjar Tohpati, Kesiman Kertalangu Village, East Denpasar, about Gerakan Masyarakat Cerdas Menggunakan Obat (Gema Cermat) which includes how to choose and get drugs properly, how to use drugs rationally, as well as how to store and dispose of drugs properly. Focus group discussion, counseling, and video screenings related to Gema Cermat were conducted, followed by training in using special preparations such as eye drops, eye ointments, insulin injection, and suppositories. The results showed an increase in cadre knowledge about Gema Cermat by 20%, from an average value of 64 at the pre-test to 80 at the post-test. This community empowerment program about Gema Cermat is expected to help both the government and the community to improve the skills and knowledge of the community in using drugs rationally.